Pretreatment-oriented PES/TEG based ultrafiltration membranes for desalination and ultra-pure water production - Seohyeon Shin; Jeonghoo Sim; Weonjung Sohn; Tae-Ok Kwon; Hyun Cheul Roh; Yun Chul Woo (Desalination, 2026)

Dual-Drug Stent with Sirolimus and WKYMVm Promotes Endothelialization and Limits Hyperplasia - Yu Jeong Jin; Dae Sung Park; Myung Ho Jeong; Doo Sun Sim; Mi Hyang Na; Chan Woo Kim; Jeong Ha Kim; Hae Jin Kee; Young Joon Hong; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; et al. (Tissue Engineering and Regenerative Medicine, 2026)

Exposure to traffic-related air pollution and the risk of premature rupture of membranes: a cohort analysis of the Korean CHildren’s ENvironmental health Study (Ko-CHENS) - Dong-Wook Lee; Kyung A. Lee; Jongmin Oh; Hwan-Cheol Kim; Sanghwan Song; Yun-Chul Hong; Eunhee Ha; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; et al. (Environmental Science and Pollution Research, 2026)

Hematology-centered physiological remodeling of black seabream (Acanthopagrus schlegelii) under gradual water temperature fluctuations - Seok-Ju Lee; Su-Mi Shin; Jae-Hyun Sim; Da-Jeong Yoo; Eunju Kim; Myung-Hwa Jung (Fish & Shellfish Immunology, 2026)

Zincophilic ultrathin Zn metal anode enabling uniform deposition and corrosion suppression in aqueous zinc ion batteries - Jong Chan Choi; Da-Eun Hyun; Jae Sol Sim; Inuk Lee; Yun Chan Kang (Chemical Engineering Journal, 2026)

Corrigendum to “Economic and demonstrative pilot-scale harvesting of microalgae biomass via novel combined process of dissolved air flotation and screw-press filtration” [Bioresour. Technol. 418 (2025) 131892] - Hyo Jik Yoon; Jeong Seop Lee; Ki Ha Min; Dong Hyun Kim; Sang Jun Sim; Seung Pil Pack (Bioresource Technology, 2026)

Optimization of Fe content of Cu–FeOX/MgAl2O4 catalyst in low-temperature reverse water–gas shift reaction for superior CO formation - Gi Dong Sim; Yeji Choi; Unho Jung; Yongha Park; Min Hye Youn; Dong Hyun Chun; Geun Bae Rhim; Kwang Young Kim; Ki Bong Lee; Kee Young Koo (Fuel, 2026)

Correction: Development of a strawberry transpiration model based on a simplified Penman–Monteith model under different irrigation regimes - Ha Seon Sim; Jung Su Jo; Yu Hyun Moon; Soo Bin Jung; Tae Yeon Lee; Ha Rang Shin; Yong Jun Kim; Na Kyong Kim; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2026)

Prediction and application on the first flowering date of June-bearing strawberry cultivars using Ensemble-based Machine learning with primary temperature values - Tae Yeon Lee; Yu Hyun Moon; Ha Seon Sim; Soo Bin Jung; Ui Jeong Woo; Ha Rang Shin; Yong Jun Kim; Na Kyoung Kim; Jung Su Jo; Sung Kyeom Kim (Computers and Electronics in Agriculture, 2026)

Nobiletin alleviates heat stress-induced meiotic arrest via restoring CDK1 and MAPK activity in porcine oocytes - Jae-Min Sim; Song-Hee Lee; Cheng-Lin Zhan; Qin-Yue Lu; Gyu-Hyun Lee; Hyeon-Ji Song; Yu-Jin Jo; Ji-Su Kim; Eui-Bae Jeung; Xiang-Shun Cui (Theriogenology, 2026)

Integrated biomarker analysis and next-generation AI for precision diabetes prediction - Hyun Sim; Hyung-Ho Ha; Hangun Kim (Toxicological Research, 2026)

Investigating eco-efficiency and its determinants in South Korean offshore fisheries - Yonghan Jeon; Hoonseok Cho; Choel-hyun Kim; Seong-hyun Sim; Eunji Kim (Fisheries Science, 2026)

Associations of pre- and postnatal levels of three heavy metals with visual impairment in 3-year-old children - Dajeong Ham; Sung Yeon Kim; Sanghyuk Bae; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; JungHeum Jo; A-Ra Jung; Seung Do Yu; Hyun Jeong Kim; et al. (Environmental Research, 2025)

Forest soil properties regulate arsenic mobility and life stage-specific ecotoxicity in Collembola: Implications for early-stage contamination risk - Hyun-Gi Min; June Wee; Yongeun Kim; Seunghun Hyun; Cheolho Sim; Han Soo Kim; Kijong Cho; Yun-Sik Lee (Journal of Hazardous Materials, 2025)

Development of a strawberry transpiration model based on a simplified Penman–Monteith model under different irrigation regimes - Ha Seon Sim; Jung Su Jo; Yu Hyun Moon; Soo Bin Jung; Tae Yeon Lee; Ha Rang Shin; Yong Jun Kim; Na Kyong Kim; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2025)

Terahertz metamaterial on-chip sensing platform for live cancer cell microenvironment analysis - Taeyeon Kim; Jisung Kwak; Yeeun Roh; Sang Jun Sim; Yong-Sang Ryu; Hyun Seok Song; Minah Seo (Chemical Engineering Journal, 2025)

Novel method for crop growth tracking with deep learning model on an Edge Rail Camera - Seungwoo Kum; Jaewon Moon; Seungtaek Oh; Hyun Kwon Suh; Hyeonji Park; Ha Seon Sim; Jung Su Jo; Sung Kyeom Kim; Seungwook Choi; Francisco Andres Pérez (Computers and Electronics in Agriculture, 2025)

Scalable electrodeposition method to construct zincophilic 3D Cu nanosheet current collector for Zn metal anode - Da-Eun Hyun; Jong Chan Choi; Jae Sol Sim; Ki Beom Kim; Yoon Ho Kim; Dae Soo Jung; Yun Chan Kang (Chemical Engineering Journal, 2025)

Economic and demonstrative pilot-scale harvesting of microalgae biomass via novel combined process of dissolved air flotation and screw-press filtration - Hyo Jik Yoon; Jeong Seop Lee; Ki Ha Min; Dong Hyun Kim; Sang Jun Sim; Seung Pil Pack (Bioresource Technology, 2025)

Impact of Arctic Sea Ice Representation on Extended Medium-Range Forecasting: a Case Study of the 2016 Barents-Kara Sea Warming Event - Jung Hyun Park; Hyun-Joon Sung; Myung-Seo Koo; Junseong Park; Rae-Seol Park; Kwang-Hee Han; Ji-Han Sim; Hyo-Jung Lee; Hayeon Noh; Baek-Min Kim (Asia-Pacific Journal of Atmospheric Sciences, 2025)

Bacterial profile-based body fluid identification using a machine learning approach - Sungmin Kim; Han Chul Lee; Jeong Eun Sim; Su Jeong Park; Hye Hyun Oh (Genes & Genomics, 2025)

Effects of Substituting Fishmeal (FM) Diet with a Diet of FM Plus Soy Protein Concentrate (SPC) Supplemented with Essential Amino Acids on the Growth and Gonadal Development of the Olive Flounder (Paralichthys olivaceus) - Sang Hyun Lee; Yu Jin Sim; Jong-Won Park; Minhwan Jeong; Julan Kim; Seong-Mok Jeong; Dain Lee; Hyun Chul Kim (Fishes, 2024)
Numerous studies have explored alternative protein sources to fishmeal (FM) to enhance fish diets, yet limited research exists on their effects on maturation. This study assessed the impact of replacing FM with soy protein concentrate (SPC) supplemented with lysine and methionine on growth and gonadal development in olive flounder (Paralichthys olivaceus). Three diets were tested: a control (Con) diet with 60% FM and two diets replacing FM with 25% (LF1) and 50% (LF2) SPC. Fish were fed to apparent satiation twice daily for 12 months. Growth performance and feed intake were not significantly different between groups. However, the gonadosomatic index varied with diet. Muscle composition and amino acid levels were similar across treatments, though n-3 fatty acids were higher in Con. Spermatogonia was increased, and spermatogenesis was impaired in SPC groups. At 12 months, oocytes in Con diets had absorbed yolk globules, whereas this was absent in SPC groups. Growth-related genes in the brain (growth hormones and insulin-like growth factor) were increased with higher SPC, while follicle-stimulating and luteinizing hormones decreased. Estrogen receptor α levels were elevated in SPC groups. Vitellogenin gene expression in gonads was highest in Con, while liver expression peaked in LF2. The expression of digestive enzymes, chymotrypsin2, and trypsin2 was highest in LF2, while lipase genes were lower. In summary, up to 50% FM replacement with SPC, with amino acid supplementation, supported growth performance and muscle composition without adverse effects on growth in olive flounder but influenced gonadal development.

MAT2A is essential for zygotic genome activation by maintaining of histone methylation in porcine embryos - Xiao-Han Li; Song-Hee Lee; Qin-Yue Lu; Cheng-Lin Zhan; Gyu-Hyun Lee; Ji-Dam Kim; Jae-Min Sim; Hyeon-Ji Song; Xiang-Shun Cui (Theriogenology, 2024)

Monkeypox virus detection using wastewater surveillance during the Mpox outbreak in the Republic of Korea - Jeong Hyun Lee; Gyuri Sim; Hye Jin Park; Minji Lee; Hwajung Yi; Yoon-Seok Chung (Journal of Environmental Chemical Engineering, 2024)

TRPA1 nanovesicle-conjugated receptonics for rapid biocide screening - Kyung Ho Kim; Jisung Kwak; Sung Eun Seo; Siyoung Ha; Gyeong-Ji Kim; Sangwoo Lee; Sang Jun Sim; Yeon Kyung Lee; Na Ly Tran; Seung Ja Oh; Woo-Keun Kim; Hyun Seok Song; et al. (Journal of Hazardous Materials, 2024)

Copper catalysts for CO2 hydrogenation to CO through reverse water–gas shift reaction for e-fuel production: Fundamentals, recent advances, and prospects - Yeji Choi; Gi Dong Sim; Unho Jung; Yongha Park; Min Hye Youn; Dong Hyun Chun; Geun Bae Rhim; Kwang Young Kim; Kee Young Koo (Chemical Engineering Journal, 2024)

Efficacy and Safety Evaluation of Tacrolimus-Eluting Stent in a Porcine Coronary Artery Model - Dae Sung Park; Mi Hyang Na; Myung Ho Jeong; Doo Sun Sim; Yu Jeong Jin; Hae Jin Kee; Mun Ki Kim; Jeong Ha Kim; Young Joon Hong; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; et al. (Tissue Engineering and Regenerative Medicine, 2024)

Chronic toxic effects of fragmented polyvinyl chloride on the water flea Moina macrocopa - Jaehee Kim; Yugyeong Sim; Jinyoung Jeong; Jee-Hyun Jung; Jae-Sung Rhee (Molecular & Cellular Toxicology, 2024)

Preliminary Investigation on Efficacy and Safety of Substance P-Coated Stent for Promoting Re-Endothelialization: A Porcine Coronary Artery Restenosis Model - Dae Sung Park; Seok Oh; Yu Jeong Jin; Mi Hyang Na; Munki Kim; Jeong Ha Kim; Dae Young Hyun; Kyung Hoon Cho; Young Joon Hong; Ju Han Kim; Youngkeun Ahn; Manuel Hermida-Prieto; et al. (Tissue Engineering and Regenerative Medicine, 2024)

Boosting oxygen evolution reaction activity with Mo incorporated NiFe-LDH electrocatalyst for efficient water electrolysis - Asiya M. Tamboli; Younghan Jung; Junseok Sim; Bonghyun Kim; Wan Sik Kim; MinJoong Kim; Changsoo Lee; Kilwon Kim; ChangHyuck Lim; KyongHwan Kim; Hyun-Seok Cho; Chang-Hee Kim (Chemosphere, 2023)

Determination of LEDs arrangement in a plant factory using a 3D ray-tracing simulation and evaluation on growth of Cucurbitaceae seedlings - Hye Jin Lee; Yu Hyun Moon; Sewoong An; Ha Seon Sim; Ui Jeong Woo; Hyunseung Hwang; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2023)

Effects of melatonin on a d-galactose-induced male reproductive aging mouse model - Won-Young Lee; Heyon Woo Sim; Hyun Jung Park (Theriogenology, 2023)

Combined effects of microplastics and benz[a]anthracene on cardiotoxicity in zebrafish (Danio rerio) larvae: Size matters - Yugyeong Sim; Hyun-Ju Cho; Jeong-Soo Lee; Wang Sik Lee; Hyunjung Kim; Jinyoung Jeong (Chemosphere, 2023)

Cream formulation improved skin-lightening effect of ginsenoside Rh1, Rg2, and Hydrangea macrophylla flower extract - Dong-Hyun Kim; Thu Nhan Nguyen; Yujin Jin; Naehwan Baek; So Young Back; Sohyun Sim; Kyung-Sun Heo; Jeong-Sook Park (Journal of Pharmaceutical Investigation, 2023)

Exposure of newborns to atmospherically relevant artificial particulate matter induces hematopoietic stem cell senescence - Govinda Bhattarai; Hyun-Jaung Sim; Han-Sol So; Jeong-Chae Lee; Sung-Ho Kook (Journal of Hazardous Materials, 2023)

Correction to: Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2023)

Preclinical Evaluation of an Everolimus-Eluting Bioresorbable Vascular Scaffold Via a Long-Term Rabbit Iliac Artery Model - Dae Sung Park; Myung Ho Jeong; Yu Jeong Jin; Mi Hyang Na; Doo Sun Sim; Munki Kim; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; Jeong Ha Kim; Kyung Seob Lim; Jun-Kyu Park; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Formation and characterization of H2-producing granule in a pilot-scale dynamic membrane bioreactor - Saint Moon Kim; Young-Bo Sim; Jong-Hyun Baik; Jisu Yang; Ashutosh Kumar Pandey; Hwan-Hong Joo; Ju-Hyeong Jung; Sang-Hyoun Kim (Chemical Engineering Journal, 2023)

Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2022)
The strawberry growth and fruit yield of five Korean cultivars in the tunnel-type greenhouse predicted using their growth. The number of leaves, petiole length, leaf length and width, crown diameter, and the ratio of red and far-red (RFR) of the five Korean cultivars were measured during the cultivation period. The number of leaves of all cultivars exhibited a similar trend during this period; the plant and petiole length of ‘Maehyang’ were the longest, leaf length exhibited similar trends in all five cultivars except for ‘Jukhyang’, the leaf width of ‘Arihyang’, was the longest, and crown diameter of ‘Keumsil’ was the thickest. The leaf length, crown diameter, and RFR were associated with the fruit yield in the multiple linear regression. When a single model was used to predict the yield of all five cultivars, the correlation between expected yield and actual yield was r = 0.53. When cultivar-specific models were built for the prediction, the correlation increased to r = 0.77. The results indicated that the fruit yield of strawberry cultivars could be better predicted by considering cultivar-specific information, so it may be necessary to consider individual cultivars specifically rather than all cultivars simultaneously.

Mechanism of protein tyrosine phosphatase 1B inhibition by theaflavanoside IV isolated from methanolic extract of tea ( Camellia sinensis ) seed shells - Hyun Sim Woo; Hyeon Jeong Im; Jeong Yoon Kim; Min-Sung Lee; Dae Wook Kim (Natural Product Research, 2022)

Reparative System Arising from CCR2(+) Monocyte Conversion Attenuates Neuroinflammation Following Ischemic Stroke - Joohyun Park; Jong Youl Kim; Yu Rim Kim; Meiying Huang; Ji Young Chang; A Young Sim; Hosung Jung; Won Taek Lee; Young-Min Hyun; Jong Eun Lee (Translational Stroke Research, 2021)
Monocytes recruitment from the blood to inflamed tissues following ischemic stroke is an important immune response to wound healing and tissue repair. Mouse monocytes can be endogenously divided into two distinct populations: pro-inflammatory or classical monocytes that express CCR2 high CX3CR1 low and circulate in blood, and anti-inflammatory or non-classical monocytes that express CCR2 low CX3CR1 high and patrol locally. In this study of transgenic mice with functional CX3CR1 GFP/+ or CX3CR1 GFP/+ -CCR2 RFP/+ , we found that CCR2 high CX3CR1 low monocytes recruited to the injured brain were cytokine-dependently converted into CCR2 low CX3CR1 high macrophages, especially under the influence of IL-4 and IL-13, thereby attenuating the neuroinflammation following sterile ischemic stroke. The overall data suggest that (1) the regulation of monocyte-switching is one of the ultimate reparative strategies in ischemic stroke, and (2) the adaptation of monocytes in a locally inflamed milieu is vital to alleviating the effects of ischemic stroke through innate immunity.

Transcriptomic analysis of the effect of (E)-3-(3,5-dimethoxyphenyl)-1-(2-methoxyphenyl) prop-2-en-1-one (DPP23) on reactive oxygen species generation in MIA PaCa-2 pancreatic cancer cells - Hongnam Sim; Euitaek Jung; Da Hyun Lee; Ji Hye Choi; Young Han Lee; Soon Young Shin (Genes & Genomics, 2020)

Gamma Aminobutyric Acid Increases Absorption of Glycine-Bound Iron in Mice with Iron Deficiency Anemia - Keun-Tae Park; Insuk Sim; Hyun-Soo Ko; Young-Hee Lim (Biological Trace Element Research, 2020)

Cardiac adaptation to exercise training in health and disease - Dae Yun Seo; Hyo-Bum Kwak; Amy Hyein Kim; Se Hwan Park; Jun Won Heo; Hyoung Kyu Kim; Jeong Rim Ko; Sam Jun Lee; Hyun Seok Bang; Jun Woo Sim; Min Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2020)

Assessment of air purifier on efficient removal of airborne bacteria, Staphylococcus epidermidis, using single-chamber method - Jung Hoon Lee; Jeong Yup Kim; Bo-Bae Cho; J. R. Anusha; Ju Yong Sim; C. Justin Raj; Kook-Hyun Yu (Environmental Monitoring and Assessment, 2019)

Cinnamomum camphora Leaves Alleviate Allergic Skin Inflammatory Responses In Vitro and In Vivo - Na-Jin Kang; Sang-Chul Han; Seok-Hyun Yoon; Jae-Yeop Sim; Young Hee Maeng; Hee-Kyoung Kang; Eun-Sook Yoo (Toxicological Research, 2019)

A 90-Day Repeated Oral Dose Toxicity Study of Alismatis Rhizoma Aqueous Extract in Rats - Mu-Jin Lee; Ho-Kyung Jung; Ki-Ho Lee; Ji-Hun Jang; Mi-Ok Sim; Tea-Gyeong Seong; Byung-Kwan Ahn; Jin-Han Shon; Seong-Ho Ham; Hyun-Woo Cho; Yong-Min Kim; Sung-Jin Park; et al. (Toxicological Research, 2019)

Beneficial Effects of Cynaroside on Cisplatin-Induced Kidney Injury In Vitro and In Vivo - Jong-Hyun Nho; Ho-Kyung Jung; Mu-Jin Lee; Ji-Hun Jang; Mi-Ok Sim; Da-Eun Jeong; Hyun-Woo Cho; Jong-Choon Kim (Toxicological Research, 2018)

Changes in the Functional Components and Radical Scavenging Activity of Korean Maize Hybrids According to Different Cropping Seasons - Hyun-Joo Kim; Mi Jung Kim; Eun-Yeong Sim; Choon Ki Lee; Yong Hee Jeon; Sun Lim Kim; Gun-Ho Jung; Beom-Young Son; Koan Sik Woo (Journal of Crop Science and Biotechnology, 2018)

Genome-wide DNA methylation profiles of maternal peripheral blood and placentas: potential risk factors for preeclampsia and validation of GRK5 - Jeong-Hyun Kim; Hyun Sub Cheong; Dae Sim Lee; Hyoung Doo Shin; Young Nam Kim (Genes & Genomics, 2017)

Glucose oxidase facilitates osteogenic differentiation and mineralization of embryonic stem cells through the activation of Nrf2 and ERK signal transduction pathways - Hyun-Jaung Sim; Jae-Hwan Kim; Sung-Ho Kook; Seung-Youp Lee; Jeong-Chae Lee (Molecular and Cellular Biochemistry, 2016)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

A novel and highly specific phage endolysin cell wall binding domain for detection of Bacillus cereus - Minsuk Kong; Jieun Sim; Taejoon Kang; Hoang Hiep Nguyen; Hyun Kyu Park; Bong Hyun Chung; Sangryeol Ryu (European Biophysics Journal, 2015)

Fabrication of an osteochondral graft with using a solid freeform fabrication system - Soon Sim Yang; Woo Hee Choi; Bo Ram Song; He Jin; Su Jeong Lee; Su Hee Lee; Junhee Lee; Young Jick Kim; So Ra Park; Sang-Hyug Park; Byoung-Hyun Min (Tissue Engineering and Regenerative Medicine, 2015)

Three dimensional plotted extracellular matrix scaffolds using a rapid prototyping for tissue engineering application - Bo Ram Song; Soon Sim Yang; He Jin; Su Hee Lee; Do Young Park; Jun Hee Lee; So Ra Park; Sang-Hyug Park; Byoung-Hyun Min (Tissue Engineering and Regenerative Medicine, 2015)

Tissue-Engineered Tracheal Reconstruction Using Mesenchymal Stem Cells Seeded on a Porcine Cartilage Powder Scaffold - Yoo Seob Shin; Jae Won Choi; Ju-Kyeong Park; Yoo Suk Kim; Soon Sim Yang; Byoung-Hyun Min; Chul-Ho Kim (Annals of Biomedical Engineering, 2015)

Temporal expression of hippocampal lysophosphatidic acid receptors and their roles in kainic acid-induced neurotoxicity - Jin-Koo Lee; Min-Soo Kwon; Hak Rim Kim; Hyung-Gun Kim; Yun-Beom Sim; Soo-Hyun Park; Hong-Won Suh (Genes & Genomics, 2014)

Normative data for neuromuscular assessment of the hand–arm vibration syndrome and its retrospective applications in Korean male workers - Ryeok Ahn; Cheol-In Yoo; Hun Lee; Chang-Sun Sim; Joo Hyun Sung; Jae-Kook Yoon; Song-Woo Shin (International Archives of Occupational and Environmental Health, 2013)

Systematic overestimation of Salicaceae seed survival using radicle emergence in response to drying and storage: implications for ex situ seed banking - Elena V. Popova; Du Hyun Kim; Sim Hee Han; Elena Moltchanova; Hugh W. Pritchard; Yong Pyo Hong (Acta Physiologiae Plantarum, 2013)

Expression of the Human Tissue-Plasminogen Activator in Hairy Roots of Oriental Melon (Cucumis melo) - Sol Kang; Hemavathi Ajjappala; Hyun-Hui Seo; Joon-Soo Sim; Sang-Hong Yoon; Bon-Sung Koo; Yong-Hwan Kim; Sukchan Lee; Bum-Soo Hahn (Plant Molecular Biology Reporter, 2011)

Inhibition of Helicobacter pylori adhesion to Kato III cells by intact and low molecular weight acharan sulfate - Joon-Soo Sim; Bum-Soo Hahn; A-Rang Im; Youmie Park; Ji-Eun Shin; Eun-Ah Bae; Dong-Hyun Kim; Yeong Shik Kim (Glycoconjugate Journal, 2011)

Evaluation of the inorganic compound leakage and carbohydrates as indicator of physiological potential of Ulmus parvifolia seeds - Du Hyun Kim; Sim Hee Han; Jeong Ho Song (New Forests, 2011)

OsPRA1 plays a significant role in targeting of OsRab7 into the tonoplast via the prevacuolar compartment during vacuolar trafficking in plant cells - Jae Bok Heo; Woo Young Bang; Se Won Kim; Sung Min Hwang; Young Sim Son; Chak Han Im; Biswa R. Acharya; Chul Wook Kim; Sam Woong Kim; Byung Hyun Lee; Jeong Dong Bahk (Planta, 2010)

The complete genome sequence and molecular analysis of human hepatitis E virus genotype IV identified from a Korean patient - Haesun Yun; Jin Seon Kim; Hyeok Jin Lee; Sook Hyang Jeong; Jeong Sim Kim; Sang Jong Park; Seong Gyu Hwang; Sook Kyoung Kang; Youngmee Jee; Jong Hyun Kim (Archives of Virology, 2010)

Effects of Escherichia coli RraA Orthologs of Vibrio vulnificus on the Ribonucleolytic Activity of RNase E In Vivo - Minho Lee; Ji-Hyun Yeom; Se-Hoon Sim; Sangmi Ahn; Kangseok Lee (Current Microbiology, 2009)